Documentul istoric depre creştinătate. Cronica medievală: analiză arhetipală - Lavinia Bănică (Revista de Istorie și Teorie Literară)
What does colliding with worlds other than their own mean for the Christians in the Middle Ages? Which are the phrases defining the Christian – Heathen opposition? How the idea of an organized Christian universe acting against the Pagan chaos is sustained? From the chronicles and other historical, oratorical or literary scholastic books to the letters sent to the Papacy or the western royal courts by the Eastern rulers, the Romanian scholars prove to be preoccupied with the portrait of the Other, the mysterious stranger speaking another language, living by different rites, praying to another God, and owning a totally different value system.